104 Effect of Mat Feeding on the Growth Performance and Morbidity and Mortality of Pigs After Weaning. (12th April 2022) - Wensley, Madie R; Tokach, Mike D; Goodband, Robert D; Gebhardt, Jordan T; Woodworth, Jason C; DeRouchey, Joel M; Allerson, Matt W; Menegat, Mariana
Abstract: Three experiments were conducted using 9, 403 pigs to determine the effect of mat feeding on growth performance and morbidity and mortality of pigs after weaning. At weaning, pigs were randomized to 96 pens (48 feeders) with 30 to 35 pigs/pen. Feeder (2 pens) was the experimental unit. For each experiment, mat feed was provided 3 times daily for 10 d and was included in calculation of post-weaning ADFI and G:F. In Exp. 1, treatments consisted of mat verses no mat feeding. Overall, mat fed pigs tended to have decreased ( P = 0.056) ADG compared with the control, which resulted in decreased ( P < 0.026) final body weights. No differences were observed in ADFI or G:F. However, mat fed pigs had reduced total mortality and removals ( P = 0.019). In Exp. 2, treatments were arranged in a 2×2 factorial with main effects of diet form (pellet or crumble) and mat feeding (without or with). Overall, no interactions between diet form and mat feeding were observed. No differences were observed in growth performance by mat feeding. However, pigs receiving pelleted feed had decreased overall ADFI ( P = 0.013) and increased G:F ( P < 0.001). Differences in total mortality and removals were not significant. In Exp. 3, treatments consisted of mat feeding small (0.32 cm) or large (1.27 cm) pellets, or no mat feeding. No differences were observed in overall ADG or G:F; however, mat fed pigs had increased ADFI ( P < 0.05), regardless of pellet size. Differences in total mortality and removals were not significant. When combining removal and mortality data for the 3 experiments, mat fed pigs had fewer total removals ( P = 0.025) compared with the control. In summary, mat feeding has limited effects on growth performance of pigs after weaning; however, mat feeding may encourage earlier feed intake reducing the fall out rate of pigs as indicated by the decreased removals.